A RARE CLINICAL SYPHILIS ORAL MANIFESTATION DUE TO SEXUALLY TRANSMITTED DISEASE AMONG HOMOSEXUAL: CASE REPORT - Agustin Ninintowe T. Santo; Riani Setiadhi; Fika Faradillah Drakel (FKG Unlam, 2023)
Background: Syphilis is a sexually transmitted disease caused by Treponema pallidum, often found in Human Immunodeficiency Virus (HIV) patients and homosexuals. The oral manifestations are chancres, mucous patches, focal epithelial hyperplasia (FEH) and papilloma/condyloma. FEH is a rare oral mucosa disorder that occurs in immunocompromised patient. Objective: To present a rare oral manifestation in syphilis patient due to sexually transmitted infections. Case: A 25-year-old homosexual male came to Oral Medicine Department complaining of sores on the palate for 3 weeks and 2 weeks later a painless lump appeared. He was an HIV patient and had been taking ARVs since 6 months ago. Pain when opening the mouth, itching on his face and genital area. Intraoral revealed a soft, pedunculated, non-bleeding, mobile mass at the palate with a diameter about 2 cm, had the same color as the surrounding tissue. There was a reddish band-like area on the maxillary anterior gingival margin, suspected as Linear Gingival Erythema (LGE). Case management: 0.2% Chlorhexidine gluconate mouthwash was administered to prevent secondary infection and he was referred to Dermatovenereology and Periodontology Department. HBsAg Immunochromatography (negative), VDRL titer (reactive), TPHA titer (reactive) therefore diagnosis of syphilis was made and he was treated with a single dose Benzathine penicillin G 2.4 million units intramuscular. The oral lesions healed after 1 month therapy. Conclusion: FEH is a rare oral mucosa disorder in syphilis patients. Knowledge of the signs and symptoms of the disease is needed to make a diagnosis and a multidisciplinary approach to achieve successful treatment. Keywords: Oral manifestation, Sexual transmission, Syphilis, Treponemal infection